2019
DOI: 10.4103/ijpvm.ijpvm_490_18
|View full text |Cite
|
Sign up to set email alerts
|

Lead poisoning in opium-addicted subjects, its correlation with pyrimidine 5′-nucleotidase activity and liver function tests

Abstract: Background:Lead may be added to the opium by drug smugglers. It can cause elevated blood lead level (BLL) in opium-addicted patients. Erythrocyte pyrimidine 5′-nucleotidase (P5N) activity is susceptible to high BLL. The aim of this study was to find out whether opium-addicted patients show erythropathy and elevated liver enzymes explainable by high BLL and decreased P5N activity.Methods:Forty orally opium-addicted subjects and 40 normal healthy volunteers were enrolled in this study. BLL was measured in whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…The reduction in Hb may be related to inhibition of its biosynthesis through the inhibition of δ-aminolevulinic acid synthase, δ-ALA dehydratase and ferrochelatase by Pb 40 . Additionally, Pb can bind with RBCs and inhibits pyruvate kinase "keeps cellular energy homeostasis" 42 and pyrimidine 5′-nucleotidase (essential for RBCs maturation) 43 . The inhibition of these enzymes destabilizes the RBCs membrane and decreases its fluidity leading to a shortage of the erythrocyte life span, hemolytic anemia, and ROS generation 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in Hb may be related to inhibition of its biosynthesis through the inhibition of δ-aminolevulinic acid synthase, δ-ALA dehydratase and ferrochelatase by Pb 40 . Additionally, Pb can bind with RBCs and inhibits pyruvate kinase "keeps cellular energy homeostasis" 42 and pyrimidine 5′-nucleotidase (essential for RBCs maturation) 43 . The inhibition of these enzymes destabilizes the RBCs membrane and decreases its fluidity leading to a shortage of the erythrocyte life span, hemolytic anemia, and ROS generation 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Pb can bind with RBCs and inhibits pyruvate kinase "keeps cellular energy homeostasis" 42 and pyrimidine 5′-nucleotidase (essential for RBCs maturation) 43 . The inhibition of these enzymes destabilizes the RBCs membrane and decreases its fluidity leading to a shortage of the erythrocyte life span, hemolytic anemia, and ROS generation 42 , 43 . High levels of ROS lead to oxidation of the cellular biomolecules, especially, the biomembrane lipids causing lipid peroxidation 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Some heavy metals can harm erythrocytes directly or can stop the formation of hemoglobin, which affects red blood cells. Its production is known to be impaired by lead [18]. These studies demonstrated increased levels of total protein and total WBCs following exposure to heavy metals like Cd, As, Pb, and Cr, which directly affected WBCs and showed increasing significance.…”
Section: Parameter Of Bloodmentioning
confidence: 94%